Corruption in Australian sport - Samantha Bricknell
Examines some of the events that have affected the integrity of Australian sport between 2009–13 to describe the way in which corruption has manifested, the environment that has engendered the corrupt behaviour and the extent to which these incidents were primarily local events involving local actors. Forward Corruption in Australian sport is not a new phenomenon. A series of high-profile cases in Australia, combined with an increasing international focus, has seen a reassessment of Australian sport’s vulnerability to illegal activities such as match-fixing, use of inside information for betting purposes and the use of performance and image-enhancing drugs. This has led to the development and endorsement of national policies on match-fixing and doping, the establishment of sport integrity units, inclusion of specialist intelligence units in law enforcement and the creation of new match-fixing offences. Yet the actual extent of corruption in Australian sport remains unclear. In particular, does it exist more in the form of a threat rather than an intrinsic or widespread problem? This paper examines some of the events that have affected the integrity of Australian sport between 2009–13 to describe the way in which corruption has manifested, the environment that has engendered the corrupt behaviour and the extent to which these incidents were primarily local events involving local actors. It also proposes situational crime prevention techniques that may assist in framing and responding to corruption in Australian sport. Adam Tomison Directo